HiG2Vec: hierarchical representations of Gene Ontology and genes in the PoincarCrossed D sign© ball - Kim, Jaesik; Kim, Dokyoon; Sohn, Kyung Ah (Bioinformatics, 2021)
Motivation: Knowledge manipulation of Gene Ontology (GO) and Gene Ontology Annotation (GOA) can be done primarily by using vector representation of GO terms and genes. Previous studies have represented GO terms and genes or gene products in Euclidean space to measure their semantic similarity using an embedding method such as the Word2Vec-based method to represent entities as numeric vectors. However, this method has the limitation that embedding large graph-structured data in the Euclidean space cannot prevent a loss of information of latent hierarchies, thus precluding the semantics of GO and GOA from being captured optimally. On the other hand, hyperbolic spaces such as the PoincarCrossed D sign